Biology : the unity and diversity of life - Starr, Cecie; Taggart, Ralph (Belmont, California : Wadsworth Publishing Company, 1987)
Contains end of chapter summaries to reinforce major concepts. Authors attempted to make chapters short enough to read in one sitting. Contains 1300 pieces of art to link illustrations to the text and case studies to show how general concepts apply to specific situations. Students taking introductory biology will not already know enough about biology to spot all key concepts in page after page of text. Major summary statements are boxed and printed in bold face for emphasis. Review questions are keyed to italic and boldfaced sentences as a way of reinforcing the main concepts. Contents in brief section gives an overview of the units contained in the full blown contents section.
Unit One. Unifying concepts in biology -- Unit Two. The cellular basis of life -- Unit Three. The ongoing flow of life -- Unit Four. Plant systems and their control -- Unit Five. Animal systems and their control -- Unit Six. Evolution -- Unit Seven. Diversity: evolutionary force, evolutionary product -- Unit Eight. Ecology and bahavior.
Includes bibliographical references and index.
Keywords: BIOLOGY